2022
DOI: 10.1371/journal.pone.0267412
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of inflammatory markers in diagnosing infected diabetic foot ulcers and diabetic foot osteomyelitis: Systematic review and meta-analysis

Abstract: Background Diabetes foot ulcer (DFU) is a complication of diabetes mellitus. Accurate diagnosis of DFU severity through inflammatory markers will assist in reducing impact on quality of life. We aimed to ascertain the diagnostic test accuracy of commonly used inflammatory markers such as erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), procalcitonin (PCT), and white cell count (WCC) for the diagnosis and differentiation between DFU grades based on the International Working Group on the Diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…We assessed for the rise in a group of markers called acute phase reactants (in particular CRP, leukocytes and thrombocytes) which the liver produces at a variable rate during states of acute and chronic inflammation. 17,18 As may be expected, this study found that inflammatory markers and acute phase reactants were raised at these patients' first presentation (mean leukocytes = 8.8±3.2 in single surgery and 9.73±4.7 in multiple surgeries; mean thrombocytes = 315.9±127.7 in single surgery and 336.07±136.3 in multiple surgeries; mean CRP = 46.8±60.1 in single surgery and 97.8±92.1 in multiple surgeries). However, a raised CRP was the only marker to be significantly associated with the requirement for further surgery, with binomial regression modelling showing a value of >84mg/L being significantly associated with requiring multiple surgical procedures.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We assessed for the rise in a group of markers called acute phase reactants (in particular CRP, leukocytes and thrombocytes) which the liver produces at a variable rate during states of acute and chronic inflammation. 17,18 As may be expected, this study found that inflammatory markers and acute phase reactants were raised at these patients' first presentation (mean leukocytes = 8.8±3.2 in single surgery and 9.73±4.7 in multiple surgeries; mean thrombocytes = 315.9±127.7 in single surgery and 336.07±136.3 in multiple surgeries; mean CRP = 46.8±60.1 in single surgery and 97.8±92.1 in multiple surgeries). However, a raised CRP was the only marker to be significantly associated with the requirement for further surgery, with binomial regression modelling showing a value of >84mg/L being significantly associated with requiring multiple surgical procedures.…”
Section: Discussionsupporting
confidence: 79%
“…We assessed for the rise in a group of markers called acute phase reactants (in particular CRP, leukocytes and thrombocytes) which the liver produces at a variable rate during states of acute and chronic inflammation 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…62 A more recent systematic review and meta-analysis published in 2022 found that PCT had the highest diagnostic test accuracy when compared to that of ESR, WBC and ESR with sensitivity, specificity, and AUC of 0.85, 0.67 and 0.844 at a cut-off value of 0.33 ng/mL. 63,95 Given the lack of inter-operator variability, the use of either ESR, CRP, or PCT as a sole biomarker for the detection of DFO in a patient with soft tissue DFI is not appropriate, but their use in combination with other diagnostic tests may be useful. A large-scale retrospective single-centre study with high risk of bias that used the results of culture and/or histology of bone samples as a reference standard found that ESR >60 mm/hr plus CRP ≥80 mg/L had a high positive predictive value, but a modest negative predictive value, for the diagnosis of DFO.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…In previous studies C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR) have been shown to perform better than newer biomarkers such as procalcitonin and interleukins to diagnose 3,4 . However, a recent meta‐analysis has shown that procalcitonin may have superior performance to both ESR and CRP in differentiating grade 2 and grade 3 diabetes‐related foot ulcerations 5 . Previous studies have also described the utility of ESR and CRP in monitoring OM 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, a recent meta-analysis has shown that procalcitonin may have superior performance to both ESR and CRP in differentiating grade 2 and grade 3 diabetes-related foot ulcerations. 5 Previous studies have also described the utility of ESR and CRP in monitoring OM. 6,7 Recently, several authors have evaluated the ratio of CRP and albumin to identify total joint infections, 8 infection versus inflammation in patients with systemic lupus erythematosus 9 and OM in diabetes-related foot infections 10 as well as to predict death.…”
mentioning
confidence: 99%